PEDAGOGICAL CONTROL OF THE TECHNICAL-TACTICAL TRAINING OF JUDO GIRLS - Esemuratova Gulmira Omirbekovna (Bright Mind Publishing, 2025)
This article presents the methods of pedagogical control of the technical and tactical preparation of female judokas based on the results of the conducted research.
Keywords: Female judokas, morphofunctional research methods, technical and tactical preparation, pedagogical test, pedagogical observation.